Validation of two game experience scales: The Player Experience of Need Satisfaction (PENS) and Game Experience Questionnaire (GEQ). Issue 118 (October 2018) - Johnson, Daniel; Gardner, M. John; Perry, Ryan
Highlights: Popular measures of videogame player experience typically have not been empirically validated. We provide factor-analytic validation of two of the most commonly used player experience scales. The theorised structure of the GEQ is partially supported; a revised five factor structure is proposed. The theorised structure of the PENS is largely supported, but we suggest combining two subscales. Abstract: Accurate measurement of the player experience in videogames is key to understanding the impacts of videogame play, designing and developing engaging videogames, and effectively applying game design principles in other fields. A large number of player experience questionnaires are available, but in most cases empirical validation of the scales is limited or absent. Two of the most commonly used scales are the Player Experience of Need Satisfaction (PENS) and the Game Experience Questionnaire (GEQ). Both scales were developed using a rational-theoretical approach, but neither scale has had formal factor-analytic studies published, limiting our capacity to judge the empirical validity of the scales. We present detailed exploratory and confirmatory factor analyses of both scales based on responses from a sample ( n = 571) of videogame players. The GEQ is partially supported (using a revised factor structure); the PENS is largely supported (with a more minor revision of the factor structure). We provide suggestions for the most effective use of both scales in future research.